Thin film light emitting device and display panel

CN119744575APending Publication Date: 2025-04-01BOE TECHNOLOGY GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480000604.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-01
Filing Date
2024-03-26
Publication Date
2025-04-01

Smart Images

  • Figure CN119744575A_ABST
    Figure CN119744575A_ABST
Patent Text Reader

Abstract

The invention provides a thin film light-emitting device and a display panel, and belongs to the technical field of display. The thin film light-emitting device comprises an anode, a hole transport layer, a light-emitting layer and a cathode which are sequentially stacked, the hole transport layer contains a hole transport material and a triplet state quenching material, and the triplet state quenching material can quench at least part of triplet state excitons in the hole transport material. The thin film light-emitting device can improve the stability of the hole transport layer. (Figure 1)
Need to check novelty before this filing date? Find Prior Art

Description

Thin film light emitting device and display panel

[0001] Cross-references

[0002] The present disclosure claims priority to Chinese patent application number 202310957423.1 filed on August 1, 2023, entitled “Thin-Film Light-Emitting Device, Preparation Method Thereof, and Display Panel”, the entire contents of which are incorporated herein by reference. Technical Field

[0003] The present disclosure relates to the field of display technology, and in particular to a thin film light emitting device and a display panel. Background Art

[0004] Quantum-dot light-emitting diodes (QDs) are a type of light-emitting display technology that has been very close to commercialization in recent years. The hole transport layer of QDs typically uses organic semiconductor materials, but these materials are easily damaged, which can lead to performance degradation in QDs.

[0005] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute prior art known to ordinary technicians in the field.

[0006] Summary of the Invention

[0007] The purpose of the present disclosure is to overcome the above-mentioned deficiencies of the prior art, provide a thin film light emitting device and a preparation method thereof, and a display panel, and improve the stability of the hole transport layer.

[0008] According to one aspect of the present disclosure, there is provided a thin film light emitting device comprising an anode, a hole transport layer, a light emitting layer and a cathode stacked in sequence;

[0009] The hole transport layer contains a hole transport material and a triplet quenching material, wherein the triplet quenching material can quench at least part of the triplet excitons in the hole transport material;

[0010] The triplet quenching material comprises a linking group and at least one quenching group connected to the linking group, and the structure of the quenching group is selected from the following structures:

[0011] Ar1 and Ar2 are each independently selected from a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, or a substituted or unsubstituted heteroaryl group having 4 to 30 carbon atoms;

[0012] R1 is selected from deuterium, an alkyloxycarbonyl group having 1 to 18 carbon atoms, an alkylcarbonyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, an alkyl group having 1 to 18 carbon atoms, a cycloalkyloxycarbonyl group having 5 to 10 carbon atoms, a cycloalkylcarbonyl group having 5 to 10 carbon atoms, a cycloalkyloxy group having 5 to 10 carbon atoms, a cycloalkyl group having 5 to 10 carbon atoms, a substituted or unsubstituted aryl group having 6 to 18 carbon atoms, and a substituted or unsubstituted heteroaryl group having 4 to 18 carbon atoms;

[0013] m is a positive integer selected from 0-7.

[0014] According to one embodiment of the present disclosure, the number of quenching groups of the triplet quenching material is 2 to 4.

[0015] According to one embodiment of the present disclosure, the quenching group of the triplet quenching material is selected from The connecting group of the triplet quenching material has an aromatic structure, and the quenching group is directly connected to the aromatic structure.

[0016] According to one embodiment of the present disclosure, Ar1 and Ar2 are each independently selected from substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl;

[0017] When Ar1 or Ar2 has a substituent, any one of the substituents is selected from deuterium, methyl, ethyl, and isopropyl.

[0018] According to one embodiment of the present disclosure, the linking group is selected from substituted or unsubstituted biphenyl, substituted or unsubstituted spirofluorenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted anthracenyl, substituted or unsubstituted phenanthrenyl, substituted or unsubstituted phenyl;

[0019] When the linking group has a substituent, any one of the substituents is independently selected from deuterium, methyl, ethyl, and isopropyl.

[0020] According to one embodiment of the present disclosure, the triplet quenching material is selected from 4,4'-bis(2,2-diphenylvinyl)-1,1'-biphenyl and 2,2`,7,7`-tetrakis(2,2-diphenylvinyl)spiro-9,9`-difluorene.

[0021] According to one embodiment of the present disclosure, the quenching group of the triplet quenching material is selected from The molecular weight of the triplet quenching material is between 600 and 1200.

[0022] According to one embodiment of the present disclosure, the linking group is an organic semiconductor structure having hole transport properties; or the linking group is a flexible linking group having at least two flexible branches, and any one of the flexible branches is connected to one of the quenching groups.

[0023] According to one embodiment of the present disclosure, the HOMO energy level of the triplet quenching material is not greater than the HOMO energy level of the hole transport material.

[0024] According to one embodiment of the present disclosure, the difference between the LUMO energy level of the triplet quenching material and the LUMO energy level of the hole transport material is not less than -1 eV.

[0025] According to one embodiment of the present disclosure, the LUMO energy level of the triplet quenching material is not less than the LUMO energy level of the hole transport material.

[0026] According to one embodiment of the present disclosure, the hole mobility of the triplet quenching material is smaller than the hole mobility of the hole transport material.

[0027] According to one embodiment of the present disclosure, the triplet energy level of the triplet quenching material is smaller than the triplet energy level of the hole transport material.

[0028] According to one embodiment of the present disclosure, the singlet energy level of the triplet quenching material is greater than the singlet energy level of the hole transport material.

[0029] According to one embodiment of the present disclosure, the mass ratio of the triplet quenching material in the hole transport layer is between 0.0001% and 90%.

[0030] According to one embodiment of the present disclosure, the mass ratio of the triplet quenching material in the hole transport layer is between 1% and 30%.

[0031] According to one embodiment of the present disclosure, the mass ratio of the triplet quenching material in the hole transport layer is between 2% and 10%. According to one embodiment of the present disclosure, the hole transport material is an organic semiconductor material; and the light-emitting layer is a quantum dot light-emitting layer.

[0032] According to one embodiment of the present disclosure, the thin film light emitting device is a blue thin film light emitting device.

[0033] According to another aspect of the present disclosure, a display panel is provided, comprising the above-mentioned thin film light emitting device.

[0034] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and those skilled in the art can derive other drawings based on these drawings without inventive effort.

[0036] FIG1 is a schematic structural diagram of a thin film light emitting device in one embodiment.

[0037] FIG2 is a schematic structural diagram of a thin film light emitting device in one embodiment.

[0038] FIG3 is a schematic structural diagram of a thin film light emitting device in one embodiment.

[0039] FIG4 is a schematic structural diagram of a thin film light emitting device in one embodiment.

[0040] FIG5 is a schematic structural diagram of a thin film light emitting device in one embodiment.

[0041] FIG6 is a luminous intensity curve of each thin film in the first verification example.

[0042] FIG. 7 is a luminous intensity curve of each thin film in the second verification example.

[0043] FIG8 is a graph showing current-voltage curves and brightness-voltage curves of test device A, test device B, and test device C. ...

[0044] FIG9 is a graph showing the current efficiency-voltage curves and the external quantum efficiency (EQE)-voltage curves of test device A, test device B, and test device C. ...

[0045] FIG10 is a diagram showing the life test and voltage test results of test device A and test device B. ...

[0046] FIG11 is a graph showing current-voltage curves and brightness-voltage curves of test device D, test device E, test device F, and test device G. ...

[0047] FIG12 is a graph showing the current efficiency-voltage curves and the external quantum efficiency (EQE)-voltage curves of test device D, test device E, test device F, and test device G. ...

[0048] FIG13 is a graph showing the life test results and voltage test results of test device D, test device E, test device F, and test device G. ... DETAILED DESCRIPTION

[0049] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that this disclosure will be thorough and complete and will fully convey the concepts of the example embodiments to those skilled in the art. Like reference numerals in the figures represent identical or similar structures, and thus their detailed descriptions will be omitted. Furthermore, the figures are merely schematic illustrations of the present disclosure and are not necessarily drawn to scale.

[0050] In this disclosure, the description “… are independently selected from” should be understood in a broad sense, which can mean that in different groups, the specific options expressed by the same symbols do not affect each other, or in the same group, the specific options expressed by the same symbols do not affect each other. For example, “ Wherein, each q is independently 0, 1, 2 or 3, and each R" is independently selected from hydrogen, deuterium, fluorine, and chlorine. The meaning is: Formula Q-1 represents that there are q substituents R" on the benzene ring, and each R" can be the same or different, and the options of each R" do not affect each other; Formula Q-2 represents that there are q substituents R" on each benzene ring of biphenyl, and the number q of R" substituents on the two benzene rings can be the same or different, and each R" can be the same or different, and the options of each R" do not affect each other.

[0051] In this disclosure, a non-localized linker refers to a single bond extending from the ring system. It means that one end of the connecting bond can be connected to any position in the ring system that the bond passes through, and the other end is connected to the rest of the compound molecule.

[0052] For example, as shown in the following formula (f), the naphthyl group represented by formula (f) is connected to other positions of the molecule through two non-positional connecting bonds that pass through the bicyclic ring, and its meaning includes any possible connection method shown in formulas (f-1) to (f-10).

[0053] For another example, as shown in the following formula (X'), the phenanthryl group represented by formula (X') is connected to other positions in the molecule through a non-positional connecting bond extending from the middle of one side of the benzene ring, and the meaning represented by it includes any possible connection method shown in formulas (X'-1) to (X'-4).

[0054] A non-positional substituent in the present disclosure refers to a substituent connected by a single bond extending from the center of the ring system, which means that the substituent can be attached at any possible position in the ring system. For example, as shown in the following formula (Y), the substituent R' represented by formula (Y) is connected to the quinoline ring by a non-positional bond, and the meaning thereof includes any possible connection method shown in formulas (Y-1) to (Y-7).

[0055] In the present disclosure, in a substituted or unsubstituted aryl group having M carbon atoms or a substituted or unsubstituted heteroaryl group having M carbon atoms, the number of carbon atoms M does not count the number of carbon atoms on the substituent, but only considers the number of carbon atoms on the aromatic ring or heteroaromatic ring. For example, An aromatic group having 6 carbon atoms substituted with a methyl group; It is an unsubstituted arylene group having 12 carbon atoms.

[0056] In the present disclosure, when no specific definition is provided otherwise, "hetero" means that a functional group includes at least one heteroatom such as B, N, O, S, Se, Si or P, and the remaining atoms are carbon, hydrogen and deuterium. The unsubstituted alkyl group may be a "saturated alkyl group" without any double or triple bonds.

[0057] In the present disclosure, "alkyl" may include straight-chain alkyl or branched-chain alkyl. An alkyl group may have 1 to 18 carbon atoms. In the present disclosure, a numerical range such as "1 to 18" refers to each integer in the given range; for example, "an alkyl group having 1 to 18 carbon atoms" refers to an alkyl group containing 1 carbon atom, 2 carbon atoms, 3 carbon atoms, 4 carbon atoms, 5 carbon atoms, 6 carbon atoms, 7 carbon atoms, 8 carbon atoms, 9 carbon atoms, 10 carbon atoms, 11 carbon atoms, 12 carbon atoms, 13 carbon atoms, 14 carbon atoms, 15 carbon atoms, 16 carbon atoms, 17 carbon atoms, or 18 carbon atoms. In some examples, the alkyl group may also be a small alkyl group having 1 to 5 carbon atoms.

[0058] Optionally, the alkyl group is selected from alkyl groups having 1 to 5 carbon atoms, and specific examples include but are not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl and pentyl.

[0059] In this disclosure, a cycloalkyl group refers to a group derived from a saturated cyclic carbon chain structure. A cycloalkyl group may have 5 to 10 carbon atoms. In this disclosure, references to numerical ranges such as "a cycloalkyl group having 5 to 10 carbon atoms" refer to each integer within the given range; for example, "a cycloalkyl group having 5 to 10 carbon atoms" refers to a cycloalkyl group having 5 carbon atoms, 6 carbon atoms, 7 carbon atoms, 8 carbon atoms, 9 carbon atoms, and 10 carbon atoms.

[0060] Alternatively, specific examples of cycloalkyl include, but are not limited to, cyclopentyl, cyclohexyl, adamantyl, norbornyl, and the like.

[0061] In the present disclosure, aryl refers to an optional functional group or substituent derived from an aromatic carbocyclic ring. Aryl can be a monocyclic aryl (e.g., phenyl) or a polycyclic aryl. In other words, aryl can be a monocyclic aryl, a condensed ring aryl, two or more monocyclic aryl groups connected by carbon-carbon conjugation, a monocyclic aryl and a condensed ring aryl connected by carbon-carbon conjugation, or two or more condensed ring aryl groups connected by carbon-carbon conjugation. That is, unless otherwise indicated, two or more aromatic groups connected by carbon-carbon conjugation can also be considered as aryl of the present disclosure. Wherein, condensed ring aryl can, for example, include bicyclic condensed aryl (e.g., naphthyl), tricyclic condensed aryl (e.g., phenanthrenyl, fluorenyl, anthracenyl), etc. Aryl does not contain heteroatoms such as B, N, O, S, P, Se, and Si. For example, in the present disclosure, biphenyl, terphenyl, etc. are aryl. Examples of aryl groups may include, but are not limited to, phenyl, naphthyl, fluorenyl, anthracenyl, phenanthrenyl, biphenyl, terphenyl, quaterphenyl, pentphenyl, benzo[9,10]phenanthrenyl, pyrenyl, benzofluoranthenyl, In the present disclosure, biphenyl can be understood as an aryl group substituted with a phenyl group, or as an unsubstituted aryl group. In the present disclosure, the arylene group refers to a divalent group formed by further losing a hydrogen atom from an aryl group.

[0062] In the present disclosure, the substituted aryl group may be an aryl group in which one or more hydrogen atoms are substituted by groups such as a deuterium atom, an aryl group, a heteroaryl group, an alkyl group, a cycloalkyl group, an alkoxy group, or the like.

[0063] In the present disclosure, a heteroaryl group refers to a monovalent aromatic ring or a derivative thereof containing at least one heteroatom in the ring, and the heteroatom can be at least one of B, O, N, P, Si, Se and S. A heteroaryl group can be a monocyclic heteroaryl group or a polycyclic heteroaryl group. In other words, a heteroaryl group can be a single aromatic ring system or a plurality of aromatic ring systems connected by carbon-carbon conjugation, and any aromatic ring system is an aromatic monocyclic ring or an aromatic condensed ring. For example, a heteroaryl group can include a thienyl group, a furyl group, a pyrrolyl group, an imidazolyl group, a thiazolyl group, an oxazolyl group, an oxadiazolyl group, a triazolyl group, a pyridyl group, a bipyridyl group, a pyrimidyl group, a triazinyl group, an acridinyl group, a pyridazinyl group, a pyrazinyl group, a quinolyl group, a quinazolinyl group, a quinoxalinyl group, a phenoxazinyl group, a phthalazinyl group, a pyridopyrimidinyl group, a pyridopyrazinyl group, a pyrazinopyrazinyl group, an isoquinolyl group, an indolyl group, a carbazolyl group, a benzoxazolyl group, a benzimidazole group, a benzofuranyl ... The present invention also includes, but is not limited to, benzothiazolyl, benzocarbazolyl, benzothiophenyl, dibenzothiophenyl, thienothiphenyl, benzofuranyl, phenanthrolinyl, isoxazolyl, thiadiazolyl, benzothiazolyl, phenothiazinyl, silafluorenyl, dibenzofuranyl, N-arylcarbazolyl (such as N-phenylcarbazolyl), N-heteroarylcarbazolyl (such as N-pyridylcarbazolyl), N-alkylcarbazolyl (such as N-methylcarbazolyl), etc. Among them, thienyl, furanyl, phenanthrolinyl, etc. are heteroaryl groups of a single aromatic ring system type, and N-arylcarbazolyl (such as N-phenylcarbazolyl) and N-heteroarylcarbazolyl are heteroaryl groups of a polycyclic system type connected by carbon-carbon bonds.

[0064] In the present disclosure, the substituted heteroaryl group may be a heteroaryl group in which one or more hydrogen atoms are substituted by groups such as a deuterium atom, an aryl group, a heteroaryl group, an alkyl group, a cycloalkyl group, an alkoxy group, or the like.

[0065] In the embodiments of the present disclosure, unless otherwise specified, the HOMO and LUMO energy levels of the compounds are measured using the same method, specifically, cyclic voltammetry. Of course, the HOMO and LUMO energy levels of the compounds can also be measured using ultraviolet photoelectron spectroscopy (UPS) or other methods.

[0066] The embodiments of the present disclosure provide a thin film light emitting device and a display panel using the thin film light emitting device. Referring to FIG1 , the thin film light emitting device includes a stacked anode AE ​​and a cathode CE, and a light emitting functional layer EFU sandwiched between the anode AE ​​and the cathode CE. Referring to FIG1 , the light emitting functional layer EFU includes at least a hole transport layer HTL and a light emitting layer, and the hole transport layer HTL is located on the side of the light emitting layer close to the anode AE. The anode and the cathode respectively provide electrons, holes and other carriers to the light emitting functional layer EFU, so that the light emitting layer of the light emitting functional layer EFU emits light. It can be understood that the type of thin film light emitting device is different, and the material and film layer of the light emitting functional layer EFU are different.

[0067] For example, referring to FIG2 , when the thin-film light-emitting device is an OLED (organic electroluminescent diode), the light-emitting functional layer EFU may include an organic light-emitting layer EML as a light-emitting layer, and may include one or more of a hole injection layer, a hole transport layer HTL, an electron blocking layer EBL, a hole blocking layer HBL, an electron transport layer ETL, and an electron injection layer EIL, and at least includes the hole transport layer HTL. Furthermore, the organic light-emitting layer EML may include a light-emitting layer host material and a light-emitting layer guest material, and the light-emitting layer guest material may be a fluorescent dopant or a phosphorescent dopant, in particular, a thermally activated delayed fluorescent material. Referring to FIG4 , when the OLED adopts a stacked structure, a charge generation layer CGL may also be provided in the light-emitting functional layer EFU.

[0068] For another example, referring to FIG3 , when the thin-film light-emitting device is a QLED (quantum dot light-emitting diode), the light-emitting functional layer EFU may include a quantum dot light-emitting layer QDL as a light-emitting layer, and may include one or more of a hole injection layer, an electron transport layer ETL, an electron blocking layer EBL, a hole blocking layer HBL, an electron transport layer ETL, and an electron injection layer EIL, and at least includes a hole transport layer HTL. The quantum dot light-emitting layer may have quantum dots. Furthermore, the quantum dots may be connected to each other through surface modification groups. Referring to FIG5 , when the QLED adopts a stacked structure, a charge generation layer CGL may also be provided in the light-emitting functional layer EFU.

[0069] In the embodiments of the present disclosure, referring to Figures 2 to 5 , the light-emitting functional layer EFU may include a single light-emitting stacked structure ELS, or may include a stack of multiple light-emitting stacked structures ELS. When the light-emitting functional layer EFU includes multiple light-emitting stacked structures ELS, a charge generation layer CGL may be provided between two adjacent light-emitting stacked structures ELS. Each light-emitting stacked structure ELS is provided with one or more light-emitting layers, which may be either an organic light-emitting layer or a quantum dot light-emitting layer.

[0070] In the examples shown in Figures 2 and 3, the light-emitting functional layer (EFU) comprises a light-emitting stacked structure (ELS). Referring to Figures 2 and 3, the thin-film light-emitting device comprises an anode (AE), a light-emitting stacked structure (ELS), and a cathode (CE) stacked in sequence. The light-emitting stacked structure (ELS) comprises a hole regulation unit, a light-emitting layer (e.g., an organic light-emitting layer (EML) or a quantum dot light-emitting layer (QDL), and an electron regulation unit stacked in sequence. The hole regulation unit is located on the side of the light-emitting layer near the anode, and the electron regulation unit is located on the side of the light-emitting layer near the cathode. The anode is used to inject holes into the light-emitting layer via the hole regulation unit, while the cathode is used to inject electrons into the light-emitting layer via the electron regulation unit. The hole regulation unit and the electron regulation unit are respectively used to adjust the injection efficiency and injection rate of holes and electrons into the light-emitting layer, as well as the energy levels of the injected electrons and holes, thereby improving the balance between hole and electron injection and thereby improving the performance of the light-emitting functional layer (EFU), such as increasing the luminous efficiency of the thin-film light-emitting device, increasing the device lifespan of the thin-film light-emitting device, and reducing the power supply voltage of the thin-film light-emitting device.

[0071] The hole regulation unit may include one or more layers of film layers such as a hole injection layer, a hole transport layer HTL, and an electron blocking layer EBL, and at least includes a hole transport layer HTL. Among them, the hole injection layer, the hole transport layer HTL, the electron blocking layer EBL, etc. are stacked in sequence along the direction from the anode to the light-emitting layer. It is understood that in some examples, one or more of the film layers such as the hole injection layer, the hole transport layer HTL, and the electron blocking layer EBL can be set as a multi-layer stacked structure. For example, the hole transport layer HTL can include a first hole transport layer and a second hole transport layer stacked, etc.

[0072] The electron regulation unit may include one or more layers of film layers such as an electron injection layer EIL, an electron transport layer ETL, and a hole blocking layer HBL, wherein the electron injection layer EIL, the electron transport layer ETL, the hole blocking layer HBL, etc. are stacked in sequence along the direction from the cathode to the light-emitting layer. It will be understood that in some examples, one or more of the film layers such as the electron injection layer EIL, the electron transport layer ETL, and the hole blocking layer HBL may be configured as a multi-layer stacked structure. For example, the electron transport layer ETL may include a first electron transport layer and a second electron transport layer stacked in layers.

[0073] In the examples of Figures 4 and 5, the light-emitting functional layer EFU has a multi-layer stacked light-emitting stack structure ELS (Figures 4 and 5 illustrate a two-layer light-emitting stack structure ELS). Referring to Figures 4 and 5, the thin-film light-emitting device includes an anode, a multi-layer stacked light-emitting stack structure ELS, and a cathode stacked in sequence. Any layer of the light-emitting stack structure ELS includes a hole regulation unit, a light-emitting layer (e.g., an organic light-emitting layer or a quantum dot light-emitting layer), and an electron regulation unit stacked in sequence, wherein the hole regulation unit is located on the side of the light-emitting layer close to the anode, and the electron regulation unit is located on the side of the light-emitting layer close to the cathode.

[0074] Optionally, the light-emitting functional layer EFU may further include a charge generation layer CGL located between two adjacent light-emitting stack structures ELS to improve the efficiency of injecting electrons and holes into the two adjacent light-emitting stack structures ELS. For example, the charge generation layer CGL includes an N-type charge generation layer NCGL and a P-type charge generation layer PCGL stacked between two adjacent light-emitting stack structures ELS. The N-type charge generation layer NCGL is arranged adjacent to the electron regulation portion of one of the light-emitting stack structures ELS, and is used to inject electrons into the electron regulation portion of the light-emitting stack structure ELS; the P-type charge generation layer PCGL is arranged adjacent to the hole regulation portion of the other light-emitting stack structure ELS, and is used to inject holes into the hole regulation portion of the light-emitting stack structure ELS. In other words, the P-type charge generation layer PCGL is arranged on the side of the N-type charge generation layer NCGL away from the anode. Of course, it can be understood that in other examples, the charge generation layer CGL may also include other structures.

[0075] It is understood that in some other embodiments of the present disclosure, the electron regulation portion of the light emitting stacked structure ELS may be omitted, or may have other structures in addition to the electron injection layer EIL, the electron transport layer ETL, and the hole blocking layer HBL.

[0076] It is understandable that when multiple light-emitting layers are provided in the light-emitting stack structure ELS, the colors of the multiple light-emitting layers may be the same or different, and the types of the multiple light-emitting layers may be the same or different.

[0077] It is understandable that, for any light-emitting stacked structure ELS, it may be provided with a light-emitting layer (such as a quantum dot light-emitting layer or an organic light-emitting layer), and may be provided with one or more of a hole injection layer, a hole transport layer HTL, an electron blocking layer EBL, a hole blocking layer HBL, an electron transport layer ETL and an electron injection layer EIL, or other film layers may be added as needed. Of course, in the light-emitting stacked structure ELS, one or more of the hole injection layer, the electron blocking layer EBL, the hole blocking layer HBL, the electron transport layer ETL and the electron injection layer EIL may also be omitted. For two light-emitting stacked structures ELS of the same thin-film light-emitting device, the film layer structures of the two light-emitting stacked structures ELS may be the same or different.

[0078] In the disclosed embodiments, a thin-film light-emitting device includes an anode, a hole transport layer, a light-emitting layer, and a cathode, stacked in sequence. The hole transport layer comprises an organic semiconductor material, such as an organic small molecule semiconductor material or a polymer semiconductor material. When electrons leak into the hole transport layer, they form excitons, including triplet excitons and singlet excitons.

[0079] Singlet excitons typically have a relatively short lifetime (e.g., 1-10 ns) and can spontaneously decay relatively quickly. Triplet excitons, however, due to the selection rule for conservation of angular momentum, have a much longer lifetime, reaching the order of microseconds or even milliseconds. Furthermore, statistically speaking, the probability of triplet exciton formation is 75%, which is greater than the 25% probability of singlet exciton formation. These factors result in a much higher concentration of triplet excitons in the hole transport layer than singlet excitons. Triplet excitons can affect the stability of the hole transport layer in various ways. At the right energy level, triplet excitons can react with trace amounts of oxygen in the film to form singlet oxygen, which can attack the unsaturated C-C bonds in the hole transport layer. Triplet excitons can undergo quenching reactions with carriers in the hole transport layer, generating high-energy carriers or excited states that have sufficient energy to attack various chemical bonds in the hole transport layer. Triplet excitons may also react with other triplet excitons or singlet excitons to generate the same high-energy state to destroy the hole transport layer.

[0080] In the disclosed embodiments, the hole transport layer (HTL) may include, in addition to the hole transport material, a triplet quenching material. The triplet quenching material can quench at least a portion of the triplet excitons in the hole transport material. Specifically, the triplet quenching material can capture triplet excitons in the hole transport layer (HTL) and convert them into a non-destructive final state, thereby reducing damage to the hole transport material caused by triplet excitons, slowing the aging of the hole transport layer (HTL), and increasing the lifespan of the thin-film light-emitting device.

[0081] Alternatively, the triplet quenching material captures triplet excitons via a Dexter charge transfer mechanism or a collision energy exchange mechanism. Furthermore, the triplet quenching material can capture triplet excitons within a 1 nm radius.

[0082] In one embodiment of the present disclosure, the thin-film light-emitting device is a blue thin-film light-emitting device. Compared to red and green thin-film light-emitting devices, the hole transport layer of a blue thin-film light-emitting device is more susceptible to damage. Therefore, introducing a triplet quenching material into the hole transport layer of the blue thin-film light-emitting device to increase the lifespan of the blue thin-film light-emitting device can more effectively alleviate the restriction of the blue thin-film light-emitting device on the lifespan of the display panel or light-emitting panel.

[0083] In one embodiment of the present disclosure, the thin-film light-emitting device is a QLED, in which the light-emitting layer is a quantum dot light-emitting layer. In this embodiment, the hole-electron transport layer can be made of an inorganic semiconductor material, such as zinc oxide or magnesium oxide, while the hole transport material is an organic semiconductor material. This makes the hole transport layer the most susceptible to damage in this QLED, limiting the device's lifespan. In this embodiment of the present disclosure, the lifetime of the QLED can be increased by adding a triplet quenching material to the hole transport layer to improve its stability.

[0084] In one embodiment of the present disclosure, the HOMO (highest occupied molecular orbital) energy level of the triplet quenching material is no greater than the HOMO energy level of the hole transport material. In this way, compared to the hole transport material, the triplet quenching material has a deeper HOMO energy level, which can avoid the generation of hole traps in the hole transport layer and ensure the smooth transmission of holes in the hole transport layer. For example, taking the hole transport material as TFB (poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-n-butyl)phenyl)-diphenylamine)]) as an example, its HOMO energy level is -5.4 eV, then the HOMO energy level of the triplet quenching material can be no greater than -5.4 eV. Of course, in other embodiments of the present disclosure, it can also be slightly higher than -5.4 eV, so as not to introduce significant hole traps.

[0085] In one embodiment of the present disclosure, the difference between the LUMO (Lowest Unoccupied Molecular Orbital) energy level of the triplet quencher material and the LUMO energy level of the hole transport material is no less than -1 eV. This prevents the LUMO energy level of the triplet quencher material from being too low, thereby creating a significant electron leakage path. For example, if the hole transport material is TFB, whose LUMO energy level is -2.8 eV, the LUMO energy level of the triplet quencher material can be no less than -3.8 eV.

[0086] Furthermore, the LUMO energy level of the triplet quenching material is greater than the LUMO energy level of the hole transport material, thereby further reducing the possibility of forming electron leakage channels.

[0087] In one embodiment of the present disclosure, the mobility of the triplet quenching material is less than the mobility of the hole transport material. In this way, the effect of the triplet quenching material on the hole transport performance of the hole transport layer can be reduced. When circumstances permit, the hole mobility of the triplet quenching material can be minimized, for example, to a value less than 1e -5 cm / V / S.

[0088] In one embodiment of the present disclosure, the triplet energy level of the triplet quenching material is lower than the triplet energy level of the hole transport material. In this way, triplet excitons on the hole transport material can be transferred to the triplet quenching material, thereby quenching the triplet excitons on the hole transport material without overcoming energy level barriers.

[0089] In one embodiment of the present disclosure, the speed at which the triplet quenching material transitions from the triplet state to the ground state is greater than the speed at which the hole transport material transitions from the triplet state to the ground state.

[0090] In one embodiment of the present disclosure, the singlet energy level of the triplet quenching material is greater than the singlet energy level of the hole transport material. Thus, the triplet quenching material does not affect the transport and blocking properties of singlet excitons in the hole transport material, effectively preserving the singlet characteristics of the host.

[0091] In one embodiment of the present disclosure, the mass ratio of the triplet quenching material in the hole transport layer is between 0.0001% and 90%. Furthermore, the mass ratio of the triplet quenching material in the hole transport layer is between 1% and 30%, for example, 1%, 2%, 5%, 10%, 15%, 20%, 25%, or 30%. In this way, the hole transport performance of the hole transport layer can be maintained as much as possible while reducing the risk of damage to the hole transport material due to triplet excitons.

[0092] In one embodiment of the present disclosure, in the hole transport layer, the hole transport material and the triplet quenching material are two independent materials, that is, there is no strong chemical bond such as a covalent bond between the two. The triplet quenching material is uniformly dispersed in the hole transport layer. In one example, a solution containing the hole transport material and the triplet quenching material can be used as a raw material to form the hole transport layer by a solution process such as coating, spin coating, printing or inkjet printing. In another example, the hole transport material and the triplet quenching material can be co-evaporated to form the hole transport layer, and the evaporation rate of the hole transport material and the triplet quenching material determines the content of the triplet quenching material in the hole transport layer.

[0093] In one example, the hole transport layer can be prepared by the following method:

[0094] dissolving the hole transport material and the triplet quenching material in a solvent to obtain a precursor solution;

[0095] The hole transport layer is prepared using the precursor solution by a coating process (e.g., spin coating process), screen printing process, or inkjet printing process. In this example, the hole transport material, triplet quenching material, and solvent are selected so that the hole transport material and triplet quenching material can be evenly distributed in the solution without aggregation, thereby facilitating the formation of a film layer with uniform thickness.

[0096] In another example, the hole transport layer can be prepared by the following method:

[0097] The hole transport material and the triplet quenching material are co-evaporated to form the hole transport layer.

[0098] For example, a hole transport material and a triplet quencher material can be placed in evaporation pools 1 and 2, respectively. The evaporation rate of the hole transport material is controlled between 0.1 angstroms and 10 nanometers per minute, and the evaporation rate of the triplet quencher is controlled between 0.1 angstroms and 10 nanometers per minute. In this way, the evaporation rate ratio of the hole transport material to the triplet quencher can be controlled between 1:1 and 1000:1, depending on the doping design. In this example, the melting point of the triplet quencher can be controlled to be less than 800°C to ensure efficient evaporation of the triplet quencher.

[0099] In another embodiment of the present disclosure, the hole transport material and the triplet quenching material are cross-linked to form a multifunctional polymer, so that the multifunctional polymer has both a segment for hole transport and a segment for quenching triplet excitons. For example, the general chemical formula of the multifunctional polymer is [A] x [B] yA represents a monomer of a hole-transporting conductive polymer, and B represents a triplet quenching material or a monomer thereof. x represents the number of repeating units of A, and y represents the number of repeating units of the triplet quenching material or a monomer thereof. The polymer may be a random dimer, a diblock polymer, or an alternating polymer.

[0100] In this way, the multifunctional polymer can be directly used as a hole transport layer, and its hole transport material and triplet quenching material are integrated into the multifunctional polymer, which can ensure the material ratio of the triplet quenching material and the uniformity of its distribution in the hole transport layer.

[0101] Optionally, A can be a TFB monomer, a PVK (English name: Poly(N-vinyl carbazole), Chinese name: Poly(N-vinyl carbazole)) monomer, a TPD (English name: (N,N'-bis(3-methylphenyl)-N,N'-diphenyl-benzidine); Chinese name: N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine)) monomer, or other monomers.

[0102] It can be understood that in the multifunctional polymer, B can be directly a monomer of a triplet quenching material, or it can be a modified triplet quenching material, and the modified triplet quenching material is a triplet quenching material monomer in which a condensation functional group (such as a double bond, isocyanate, etc.) is introduced so that the modified triplet quenching material can polymerize with A.

[0103] In one example, a triplet quenching material can be linked to a polymer serving as a hole transport material through chemical synthesis to form a new polymer.

[0104] In another example, the monomers of the triplet quenching material and the monomers of the hole transporting material may be polymerized together to generate a desired polymer.

[0105] In one example, the hole transport layer can be prepared by the following method:

[0106] polymerizing the monomer of the hole transport material and the monomer of the triplet quenching material to form a multifunctional polymer;

[0107] dissolving the multifunctional polymer in a solvent to obtain a precursor solution;

[0108] The hole transport layer is prepared using the precursor liquid by a coating process, a screen printing process or an inkjet printing process.

[0109] In other embodiments, the triplet quenching material is connected to at least a portion of the hole transport material via a chemical bond or a linking group. In this embodiment, a multifunctional material can be synthesized first. The multifunctional material is a material formed by connecting a hole transport material and a triplet quenching material via a chemical bond or a linking group. For example, the structure of the multifunctional material is a structure formed by directly connecting the hole transport material and the triplet quenching material via a chemical bond (e.g., a single bond), or a structure formed by connecting the hole transport material and the triplet quenching material via a linking group (e.g., a methylene group, a phenylene group, etc.). It is understood that it is not necessary to use a hole transport material and a triplet quenching material as raw materials to synthesize the desired multifunctional material. The structure of the synthesized material is that the multifunctional material is interconnected as a hole transport material and a triplet quenching material. The multifunctional material has both hole transport and triplet quenching functions. When preparing the hole transport layer, the hole transport material and the multifunctional material can be used as raw materials. For example, a mixture of the hole transport material and the multifunctional material (evaporation material) is co-evaporated to form the hole transport layer.

[0110] For example, the hole transport material is A, the triplet quenching material is B, and the multifunctional material is AB. When the hole transport layer is prepared by evaporation, the evaporation source material is A with a mass content x, and AB with a mass content 1-a. x is a positive number less than 1. By adjusting a, the mass content of the triplet quenching material in the hole transport layer can be adjusted.

[0111] It is understandable that one multifunctional material may be connected to one triplet quenching material or multiple triplet quenching materials.

[0112] In one example, the hole transport layer can be prepared by the following method:

[0113] synthesizing a multifunctional material, wherein the multifunctional material is a material formed by connecting the hole transport material and the triplet quenching material via a chemical bond or a linking group;

[0114] uniformly mixing the multifunctional material and the hole transport material to form an evaporation material;

[0115] The hole transport layer is formed by using the evaporation material and adopting an evaporation process.

[0116] Optionally, the triplet quenching material includes one or more of transition metal derivatives, acene, acene derivatives, cyclooctadiene, cyclooctadiene derivatives, cyclooctatetraene, cyclooctatetraene derivatives, organic small molecule semiconductor materials, and polymer semiconductor materials.

[0117] In one embodiment of the present disclosure, the transition metal derivative may be a transition metal chelate. For example, it may be a nickel derivative, particularly a nickel chelate. Of course, it may also be a chelate of other transition metals, such as a zinc chelate.

[0118] For example, the triplet quenching material is selected from the following compounds:

[0119] Nickel chelates have multiple triplet quenching mechanisms, which can quench triplet excitons of at least 1.1eV without affecting singlet excitons in hole transport materials. The quenching rate can reach 10 8 Furthermore, nickel chelates can sometimes quench free radicals and decompose peroxides, further enhancing the protection of hole transport materials.

[0120] Acene and its derivatives typically have a large gap between singlet and triplet energy levels, allowing them to quench triplet states in hole transport materials while maintaining singlet states. For example, anthracene has a singlet energy level of 3.1 eV and a triplet energy level of 1.78 eV.

[0121] Cyclooctatetraene (COT) is a non-classical triplet quencher. In addition to possessing a high triplet excited state (energy level of 2.56 eV), it also exhibits a very low triplet energy level (energy level of 0.8 eV) during relaxation, making it highly effective in quenching triplets in host materials. Furthermore, its high singlet energy level (4.39 eV) does not affect singlet states in hole transport materials or charge transport within them. Cyclooctatetraene's triplet lifetime is shorter than that of anthracene, allowing it to rapidly decay triplet states accepted from hole transport materials.

[0122] BSBCZ has a low triplet energy level (1.48 eV) and a high singlet energy level (2.97 eV). BSBCZ is a representative of a more traditional and widely used small molecule or polymer semiconductor material that can serve as a triplet quencher. The energy levels of these triplet quenchers must match those of the hole transport material. For example, the triplet energy level of the triplet quencher must be lower than that of the hole transport material. Ideally, the singlet energy level of the triplet quencher should be higher than that of the hole transport material, with the HOMO energy level of the triplet quencher lower than that of the hole transport material, and the LUMO energy level of the triplet quencher higher than that of the hole transport material.

[0123] In some embodiments of the present disclosure, the triplet quenching material includes a linking group and at least one quenching group connected to the linking group, and the structure of the quenching group is selected from the following structures:

[0124] Ar1 and Ar2 are each independently selected from a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, or a substituted or unsubstituted heteroaryl group having 4 to 30 carbon atoms.

[0125] In this embodiment, The group is beneficial for the triplet quenching material to obtain appropriate HOMO energy level, LUMO energy level, singlet energy level, and triplet energy level.

[0126] In some examples of this embodiment, the substituents on Ar1 and Ar2 can be independently selected from deuterium, methyl, ethyl, isopropyl, methoxy, ethoxy, cyclohexyl, cyclopentyl, and adamantyl.

[0127] In some examples of this embodiment, the quenching group of the triplet quenching material is selected from The linking group of the triplet quenching material has an aromatic structure (such as a benzene ring, a fluorene ring, a naphthalene ring, etc.), and the quenching group is directly connected to the aromatic structure. Conjugation can further adjust the HOMO energy level, LUMO energy level, singlet energy level, triplet energy level, etc. of the triplet quenching material, so that the energy levels of the triplet quenching material and the hole transport material are better matched.

[0128] In one example, Ar1 and Ar2 are each independently selected from a substituted or unsubstituted phenyl group, a substituted or unsubstituted naphthyl group, or a substituted or unsubstituted biphenyl group; when Ar1 or Ar2 has a substituent, any of the substituents is selected from deuterium, methyl, ethyl, or isopropyl. For example, Ar1 and Ar2 are each independently selected from a deuterium-substituted or unsubstituted phenyl group, a deuterium-substituted or unsubstituted naphthyl group, or a deuterium-substituted or unsubstituted biphenyl group.

[0129] In one example, the linking group is selected from substituted or unsubstituted biphenyl, substituted or unsubstituted spirofluorenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted anthracenyl, substituted or unsubstituted phenanthrenyl, and substituted or unsubstituted phenyl; when the linking group has a substituent, any one of the substituents is independently selected from deuterium, methyl, ethyl, and isopropyl. For example, the linking group is selected from deuterium-substituted or unsubstituted biphenyl, deuterium-substituted or unsubstituted spirofluorenyl, deuterium-substituted or unsubstituted terphenyl, deuterium-substituted or unsubstituted naphthyl, deuterium-substituted or unsubstituted anthracenyl, deuterium-substituted or unsubstituted phenanthrenyl, and deuterium-substituted or unsubstituted phenyl.

[0130] In some examples of this embodiment, the triplet quenching material has 2 to 4 quenching groups. This allows the energy level of the triplet quenching material to be adjusted through the interaction between the quenching groups. Furthermore, it improves the quenching efficiency of the triplet quenching material, thereby enhancing the stability of the triplet quenching material itself. Furthermore, this helps reduce the doping level of the triplet quenching material in the hole transport layer, reducing the impact of the triplet quenching material on the hole transport performance of the hole transport layer.

[0131] In one example, the triplet quenching material is selected from 4,4′-bis(2,2-distyryl)-1,1′-biphenyl (compound DPVBi) and 2,2′,7,7′-tetrakis(2,2-diphenylvinyl)spiro-9,9′-bifluorene (compound Spiro-DPVBi).

[0132] The structures of compound DPVBi and compound Spiro-DPVBi are as follows:

[0133] In this example, the compound Spiro-DPVBi is a spiro-linked derivative of the compound DPVBi. In other examples, the triplet quenching material can also be another derivative of the compound DPVBi, such as one in which the compound DPVBi is chemically bonded or linked to a hole transport material, or one in which the compound DPVBi is substituted with an alkyl group, an aryl group, a heteroaryl group, or a deuterium group. These derivatives of the compound DPVBi can retain similar energy level characteristics to the compound DPVBi while also improving certain properties, such as film-forming properties.

[0134] The following describes the characteristic parameters of DPVBi and Spiro-DPVBi as examples to illustrate the structure of DPVBi and its derivatives. In this example, the polymer TFB (poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-n-butyl)phenyl)-diphenylamine)])) is used as a hole transport material.

[0135] In this example, the compound DPVBi has an S1 energy level of 3.1 eV, a T1 energy level of 2.2 eV, a LUMO energy level of -2.8 eV, and a HOMO energy level of -5.8 eV. The compound Spiro-DPVBi has a T1 energy level of 1.98 eV, a LUMO energy level of -2.4 eV, and a HOMO energy level of -5.4 eV. Correspondingly, the compound TFB has an S1 energy level of 2.8 eV, a T1 energy level of 2.3 eV, a LUMO energy level of -2.8 eV, and a HOMO level of -5.4 eV.

[0136] Thus, when compound DPVBi is used in conjunction with compound TFB, compound TFB can function as a hole transport material, and compound DPVBi can function as a triplet quencher. The HOMO energy level of compound DPVBi is lower than that of compound TFB; the LUMO energy level of compound DPVBi is no lower than that of compound TFB; the T1 energy level of compound DPVBi is lower than that of compound TFB; and the S1 energy level of compound DPVBi is higher than that of compound TFB.

[0137] In one example of the present disclosure, a test device (red QLED device) was prepared and tested according to the following method.

[0138] Step A1) Solution Preparation: Prepare a PEDOT:PSS solution, prepare a mixed solution of TFB and DPVBi (12 mg / mL, in chlorobenzene solvent, three different mixed solutions, with the mass ratio of DPVBi in (DPVBi + TFB) in the different mixed solutions being 0%, 2%, and 10%, respectively), and prepare a ZnO nanoparticle solution (in isopropanol solvent).

[0139] Step A2) Substrate preparation: The ITO patterned substrate was ultrasonically cleaned in water for 600 seconds, then in isopropyl alcohol for 300 seconds, and then treated in UV Ozone for 15 minutes.

[0140] Step A3) Spin coating the hole injection layer: Spin coating the PEDOT:PSS hole injection layer at a speed of 3000 rpm for 1 min.

[0141] Step A4) Transfer to an inert environment: The glove box is thoroughly purged to ensure low oxygen and water content. The device is transferred to an inert environment.

[0142] Step A5) Spin coating the hole transport layer: Spin coating the prepared TFB:DPVBi mixed solution at a rate of 2000 rpm for 1 minute. Anneal at 120 degrees Celsius for 10 minutes.

[0143] Step A6) Spin coating the quantum dot light-emitting layer: concentration 20 mg / ml, spin coating rate 2000 rpm, time 1 min, annealing at 100 degrees Celsius for 10 minutes.

[0144] Step A7) Spin coating ZnO nanoparticle material: spin coating rate is 2000 rpm, time is 1 min, and annealing is performed at 100 degrees Celsius for 10 minutes.

[0145] Step A8) Vacuum thermal evaporation of 100 nm Al as the top electrode.

[0146] Step A9) Encapsulation and testing using glass plates and epoxy resin.

[0147] In this example, basically identical test devices A, B and C were prepared, and the only difference between test devices A, B and C was that the mass ratio of the mass of DPVBi in the hole transport layer to the total mass of DPVBi and TFB (in the embodiment of the present disclosure, this is referred to as the doping ratio for convenience of expression) was 0%, 2% and 10%, respectively.

[0148] Figure 8 shows the current-voltage and brightness-voltage curves for test devices A, B, and C. As shown in Figure 8, compared to test device A, the forward leakage currents of test devices B and C before turn-on (approximately 1.8V) are significantly reduced, with the reduction for test device B exceeding an order of magnitude. Furthermore, after the devices are turned on, the forward turn-on currents of test devices B and C do not decrease. This indicates that the addition of DPVBi does not affect the charge transfer of the devices.

[0149] Figure 9 shows the current efficiency-voltage curves and external quantum efficiency (EQE)-voltage curves for test devices A, B, and C. As shown in Figure 9, the peak EQE for test device A is approximately 19%, while that for test device B increases to approximately 22.5%, an 18% improvement. The peak EQE for test device C is approximately 18%, indicating that excessive DPVBi doping may affect the external quantum efficiency. For example, a moderate DPVBi doping level can improve hole injection through its deeper HOMO energy level, while excessive DPVBi doping may reduce the hole transport capability of the hole transport layer, thereby affecting charge balance.

[0150] Figure 10 shows the life test and voltage test results of test device A and test device B. In this test, both devices were lit at high brightness (both close to 10,000 nits) and tested for changes in voltage and brightness over time. According to Figure 10, it can be seen that the T95 life (the time it takes for the brightness to decay to 95% of the maximum brightness) of test device A is greater than 25 hours, while the T95 life of test device B is greater than 90 hours. Therefore, the life of the device doped with DPVBi is significantly improved. At the same time, considering that the external quantum efficiency is increased by nearly 18%, the improvement in device life mainly comes from the improvement in the stability of the hole transport layer.

[0151] In the above examples, devices with 2% DPVBi and 10% DPVBi doped hole transport layers were prepared and tested. It will be appreciated that devices with other doping ratios can also be prepared, such as 0.5%, 1%, 1.5%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, and 9.5%.

[0152] In the above example, chlorobenzene was used as the solvent when preparing the hole transport layer. In other embodiments of the present disclosure, the solvent can be adjusted to adjust the distribution of DPVBi in the hole transport layer and on the surface, thereby further adjusting the performance of the device.

[0153] In other examples, after forming the hole transport layer, the surface of the hole transport layer can be rinsed with a washing solution to adjust the DPVBi content on the surface of the hole transport layer, such as reducing the DPVBi at the interface between the hole transport layer and the quantum dot layer. This helps optimize the energy level arrangement at the interface, such as reducing leakage that may be caused by DPVBi. Alternatively, the surface of the hole transport layer can be rinsed with a solvent having a different polarity than the solvent in the mixed solution of TFB and DPVBi, or with a solvent having a different polarity than the solvent in the quantum dot solution (e.g., octane).

[0154] In some cases, you can also use the above example method to replace DPVBi with Spiro-DPVBi to achieve better performance. Compared with DPVBi, Spiro-DPVBi has the following advantages:

[0155] a) The energy level match is better, and the triplet state quenching effect is better; the triplet state energy level of spiro-DPVBi is 1.98 eV, which is more different from the triplet state energy level of TFB. From the perspective of energy dynamics, it has a better quenching effect on triplet excitons;

[0156] b) The molecular volume is larger, at least twice as large as DPVBi, resulting in better film-forming performance and the ability to prevent the crystallization of the transport material. Especially for crystalline hole transport materials, spiro-DPVBi's large molecular weight (reaching the kg / mol level) and large volume (approximately 2-3nm) with a bond length of more than ten atoms can effectively interfere with the crystallization of the hole transport material and improve the smoothness of the film.

[0157] In some other embodiments of the present disclosure, the triplet quenching material includes a linking group and at least one quenching group connected to the linking group, and the structure of the quenching group is selected from the following structures:

[0158] R1 is selected from deuterium, an alkyloxycarbonyl group having 1 to 18 carbon atoms, an alkylcarbonyl group having 1 to 18 carbon atoms, an alkoxy group having 1 to 18 carbon atoms, an alkyl group having 1 to 18 carbon atoms, a cycloalkyloxycarbonyl group having 5 to 10 carbon atoms, a cycloalkylcarbonyl group having 5 to 10 carbon atoms, a cycloalkyloxy group having 5 to 10 carbon atoms, a cycloalkyl group having 5 to 10 carbon atoms, a substituted or unsubstituted aryl group having 6 to 18 carbon atoms, and a substituted or unsubstituted heteroaryl group having 4 to 18 carbon atoms;

[0159] m is a positive integer selected from 0-7.

[0160] In this embodiment, the triplet quenching material is a COT (cyclooctatetraene) derivative, wherein the cyclooctatetraene group exhibits a triplet quenching effect. The substituents and linking groups on the cyclooctatetraene group can adjust the energy levels, physical properties (e.g., melting point, volume, boiling point), and chemical properties (e.g., electrochemical stability, aging rate), of the triplet quenching material, thereby matching the physical and chemical properties and energy levels of the triplet quenching material with those of the hole transport material.

[0161] In one example of this embodiment, the molecular weight of the triplet quenching material is between 600 and 1200. This can avoid the problem of the triplet quenching material having a too low melting point (which would result in a low glass transition temperature of the film layer), thereby improving the film formation stability of the hole transport layer.

[0162] In an example of this embodiment, the linking group is an organic semiconductor structure having hole transport properties; or the linking group is a flexible linking group having at least two flexible branches, and any one of the flexible branches is connected to one of the quenching groups.

[0163] For example, in one example, one or more triarylamine compounds can be modified. This can make the triarylamine compound have a triplet quenching effect. They are connected by non-conjugated bonds to reduce the effect of conjugation on the energy level of COT.

[0164] For another example, in one example, the linking group may have a central quaternary carbon, to which four flexible branches (such as alkyl branches) are connected, and each end of the flexible branch is connected to This can modify COT while increasing the content of COT groups, thereby improving the triplet quenching effect.

[0165] The disclosed embodiments also provide a verification example to verify the protective effect of adding a triplet quenching material to the hole transport material on the hole transport material.

[0166] First verification example:

[0167] The hole transport material is a polymer TFB (Poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-butylphenyl)), Chinese name: Poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-n-butyl)phenyl)-diphenylamine)]), and the triplet quenching material is UV-1084 (chemical full name: 2,2′-Thiobis(4-tert-octylphenolato)-n-butylamine nickel(II), Chinese name: 2,2-Thiobis(4-tert-octylphenol)n-butylamine nickel salt).

[0168] Among them, the structure of UV-1084 is shown as:

[0169] The hole transport material and the triplet quenching material were co-dissolved in chlorobenzene to obtain a hole transport layer precursor. The ITO patterned glass substrate was subjected to UV treatment and ozone treatment. PEDOT:PSS was then spin-coated at a speed of 3000 rpm for 1 minute; then, the device was annealed at 150°C in air for 30 minutes to form a hole injection layer. The device was transferred to an inert environment and spin-coated with the above-mentioned hole transport layer precursor. The concentration of the material (hole transport material + triplet quenching material) in the precursor was 12 mg / mL, the spin coating rate was 2000 rpm, the spin coating time was 1 minute, and the device was annealed at 120°C for 10 minutes to obtain a hole transport layer film for testing.

[0170] In this demonstration example, a first verification film, a second verification film, and a first reference film were prepared. The first verification film contained 5% triplet quenching material by weight; the second verification film contained 10% triplet quenching material by weight; and the first reference film contained no triplet quenching material.

[0171] The first verification film, the second verification film and the reference film are irradiated with detection light (low intensity), aging light (high intensity) and detection light (low intensity) in turn. The wavelength of the irradiation light can be 405 nanometers. At the same time, the intensity of the light emitted by the hole transport material after being excited is detected. The light intensity can reflect the degree of damage to the hole transport material. The stronger the light intensity, the less damage to the hole transport material, and the better the protection effect of the triplet quenching material on the hole transport material. Among them, the hole transport material generates photogenerated excitons after being irradiated with light, and the triplet quenching material can protect the hole transport material by quenching triplet excitons. The verification test results are shown in Figure 6.

[0172] Referring to Figure 6, when the film is irradiated with a relatively low intensity test light, all three films are excited and emit light under the light. However, it is obvious that the luminescence intensity of the first reference film C10, to which no triplet quenching material is added, decreases relatively quickly, while the luminescence intensity of the first verification film C11 and the second verification film C12 is maintained relatively well. This shows that the triplet quenching material has a good protective effect on the hole transport material. When the film is irradiated with a higher intensity aging light, the luminescence intensity of the three films is, from large to small, the second verification film C12, the first verification film C11, and the first reference film C10. This shows that the stability of the film added with the triplet quenching material under strong light is greatly improved, and the stability of the film is correlated with the amount of triplet quenching material added. Within a certain content range, the more triplet quenching material is added, the better the stability of the hole transport material.

[0173] In the above verification example, the intensity of the detection light is 100 mW / cm², and the intensity of the aging light is 10 W / cm². It is understood that, as needed, the intensity of the detection light and the intensity of the aging light can be adjusted so that the intensity of the aging light is 10 to 1000 times greater than the intensity of the detection light, for example, the intensity of the aging light is 100 times greater than the intensity of the detection light. Alternatively, the intensity of the detection light is in the range of 0.1 to 100 mW / cm², and the intensity of the aging light is in the range of 5 mW / cm² to 100 W / cm².

[0174] Second verification example

[0175] Following the same principles as in the first verification example, second, third, fourth, fifth, and sixth reference films were prepared. The second reference film did not contain a triplet quencher, and its hole transport material was TFB. The third, fourth, fifth, and sixth verification films contained methyl 1,3,5,7-cyclooctatetraene-1,2-dicarboxylate, with a mass content of 2%, 5%, 10%, and 20%, respectively. Each film had a thickness of approximately 20 nm.

[0176] Among them, the structural formula of 1,3,5,7-cyclooctatetraene-1,2-dicarboxylic acid methyl ester (hereinafter referred to as COT1) is:

[0177] Each film was sequentially irradiated with detection light (low intensity), aging light (high intensity), and detection light (low intensity), with the wavelength of the irradiation light being 405 nanometers. At the same time, the intensity of the light emitted by the hole transport material after excitation was detected, which can reflect the degree of damage to the hole transport material. The stronger the light intensity, the less damage to the hole transport material and the better the protection effect of the triplet quenching material on the hole transport material. Among them, the hole transport material generates photogenerated excitons after being irradiated with light, and the triplet quenching material can protect the hole transport material by quenching the triplet excitons. The verification test results are shown in Figure 7.

[0178] As shown in Figure 7, when a triplet quencher is added to the film, the film's stability under strong light is significantly improved. This indicates that the triplet quencher can protect the hole transport material.

[0179] In one example of the present disclosure, a test device (red QLED device) was prepared and tested according to the following method.

[0180] Step B1) Solution Preparation: Prepare a PEDOT:PSS solution, prepare a mixed solution of TFB and COT1 (12 mg / mL, in chlorobenzene solvent, for a total of four different mixed solutions, with the mass ratio of COT1 in the (COT1 + TFB) in the different mixed solutions being 0%, 5%, 10%, and 20%, respectively), and prepare a ZnO nanoparticle solution (in isopropanol solvent).

[0181] Step B2) Substrate preparation: The ITO patterned substrate was ultrasonically cleaned in water for 600 seconds, then in isopropyl alcohol for 300 seconds, and then treated with UV Ozone for 15 minutes.

[0182] Step B3) Spin coating the hole injection layer: Spin coating the PEDOT:PSS hole injection layer at a rate of 3000 rpm for 1 min.

[0183] Step B4) Transfer to an inert environment: The glove box is thoroughly purged to ensure low oxygen and water content. The device is transferred to an inert environment.

[0184] Step B5) Spin coating the hole transport layer: Spin coating the prepared TFB:COT1 mixed solution at a rate of 2000 rpm for 1 minute, followed by annealing at 120 degrees Celsius for 10 minutes.

[0185] Step B6) Spin coating the quantum dot light-emitting layer: the concentration is 20 mg / ml, the spin coating rate is 2000 rpm, the time is 1 min, and the annealing treatment is performed at 100 degrees Celsius for 10 minutes.

[0186] Step B7) Spin coating ZnO nanoparticle material: the spin coating rate is 2000 rpm, the time is 1 min, and the material is annealed at 100 degrees Celsius for 10 minutes.

[0187] Step B8) Vacuum thermal evaporation of Al with a thickness of about 100 nm as the top electrode.

[0188] Step B9) Encapsulation and testing using glass plates and epoxy resin.

[0189] In this example, basically identical test devices D, E, F, and G were prepared. The only difference between test devices D, E, F, and G was that the mass ratio of COT1 in the hole transport layer to the total mass of COT1 and TFB (in the embodiment of the present disclosure, this is referred to as the doping ratio for convenience of expression) was 0%, 5%, 10%, and 20%, respectively.

[0190] Figure 11 shows the current-voltage curves and brightness-voltage curves of test devices D, E, F, and G. Referring to Figure 11 , the current and brightness of test device E are similar to those of test device D, while the current and brightness of test devices F and G are both greater than those of test device D.

[0191] Figure 12 shows the current efficiency-voltage curves and external quantum efficiency (EQE)-voltage curves for test devices D, E, F, and G. Referring to Figure 12 , the efficiency of test device E is slightly higher than that of test device D, while the efficiencies of test devices F and G are slightly lower than that of test device D.

[0192] Figure 13 shows the lifespan and voltage test results for test devices D, E, F, and G. In this test, all four devices were illuminated at full brightness, and after reaching maximum brightness, their brightness changes were monitored to determine the degree of brightness decay. This test shows that test device E has a longer lifespan than test device D, while test devices F and G have a shorter lifespan than test device D.

[0193] It's understandable that although COT1 is a solid at room temperature, its low boiling point makes it susceptible to instability, leading to insufficient film stability when formed with hole transport materials. Therefore, COT compounds can be modified to improve their stability, for example, by obtaining COT derivatives with higher boiling points, which can be more effectively used in conjunction with hole transport materials.

[0194] The following describes the structure, materials, and preparation method of the thin-film light-emitting device in the embodiment of the present disclosure by taking multiple embodiments as examples.

[0195] Example 1

[0196] A thin-film light-emitting device includes an anode, a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer, and a cathode, stacked in sequence. In this example, the anode is made of ITO; the hole transport layer is made of PEDOT:PSS; the hole transport layer is made of a mixture of TFB and UV-1084; the electron transport layer is made of zinc oxide; and the cathode is made of aluminum.

[0197] The thin film light emitting device can be prepared by the following method.

[0198] 1) TFB and UV-1084 were dissolved in chlorobenzene to obtain a hole transport layer precursor solution; the total mass concentration of TFB and UV-1084 in the precursor solution was 12 mg / mL; and the mass proportion of UV-1084 in the film-forming material (UV-1084+TFB) was 1%.

[0199] 2) UV treatment and ozone treatment are performed on the patterned ITO substrate (ITO layer + glass layer).

[0200] 3) Spin coating PEDOT:PSS at a rotation speed of 3000 rpm for 1 minute, followed by annealing at 150° C. in air for 30 minutes to form a hole injection layer.

[0201] 4) The device was transferred to an inert environment, and a hole transport layer precursor solution was spin-coated at a rotation speed of 2000 rpm for 1 minute; then, the device was annealed at 120° C. for 10 minutes to form a hole transport layer.

[0202] 5) Spin coating a quantum dot liquid with a quantum dot content of 20 mg / mL, a rotation speed of 2000 rpm, and a spinning time of 1 minute; then annealing at 100° C. for 10 minutes to form a quantum dot light-emitting layer.

[0203] 6) Spin-coating a zinc oxide precursor solution at a rotation speed of 2000 rpm for 1 minute; then annealing at 100° C. for 10 minutes to obtain an electron transport layer.

[0204] 7) Evaporated cathode, made of aluminum with a thickness of 100 nm.

[0205] Example 2

[0206] A thin-film light-emitting device includes an anode, a hole injection layer, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer, and a cathode, stacked in sequence. In this example, the anode is made of ITO; the hole transport layer is made of PEDOT:PSS; the electron transport layer is made of zinc oxide; and the cathode is made of aluminum. The hole transport layer is made of the following multifunctional polymers:

[0207] Wherein, x represents the number of repeating units of the TFB monomer, which is 200; y represents the number of repeating units of the cyclooctatetraene derivative monomer, which is 2.

[0208] In this example, the hole transport material and the triplet quenching material are cross-linked to form a multifunctional polymer, such that the multifunctional polymer has a hole transport segment and a triplet quenching segment.

[0209] In this embodiment, a thin-film light-emitting device can be prepared by referring to the preparation method of Example 1, except that the multifunctional polymer of this embodiment is used as the film-forming material when preparing the hole transport layer precursor solution. The mass concentration of the film-forming material in the hole transport layer precursor solution is 12 mg / mL.

[0210] Example 3

[0211] The thin-film light-emitting device includes an anode, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer, and a cathode, stacked in sequence. In this example, the anode is made of molybdenum oxide / silver; the hole transport layer is made of anthracene-doped CBP; the electron transport layer is made of zinc oxide; and the cathode is made of indium tin oxide (ITO).

[0212] The structure of CBP is as follows:

[0213] The thin film light emitting device can be prepared by the following method.

[0214] 1) UV treatment and ozone treatment were performed on a patterned ITO substrate (ITO layer + glass layer).

[0215] 2) Spin coating a zinc oxide precursor solution at a rotation speed of 2000 rpm for 1 minute; and then annealing at 100° C. for 10 minutes to obtain an electron transport layer.

[0216] 3) Spin coating a quantum dot liquid, wherein the quantum dot content in the quantum dot liquid is 20 mg / mL, the rotation speed is 2000 rpm, and the rotation time is 1 minute; then annealing at 100° C. for 10 minutes to form a quantum dot light-emitting layer.

[0217] 4) A stable hole transport layer was formed by co-evaporation process. Source 1 used CBP (evaporation rate was 1 nm / min) and source 2 used anthracene (evaporation rate was 0.1 nm / min), and the co-evaporation was 50 nm.

[0218] 5) Evaporated cathode, the material is molybdenum oxide / silver, with a thickness of 3nm / 100nm.

[0219] Example 4

[0220] The thin-film light-emitting device includes an anode, a hole transport layer, a quantum dot light-emitting layer, an electron transport layer, and a cathode, stacked in sequence. In this example, the anode is made of molybdenum oxide / silver; the hole transport layer is a mixture of CPB and COT-modified CPB; the electron transport layer is made of zinc oxide; and the cathode is made of indium tin oxide (ITO).

[0221] The structure of COT-modified CPB (multifunctional material) is as follows:

[0222] The thin film light emitting device can be prepared by the following method.

[0223] 1) UV treatment and ozone treatment were performed on a patterned ITO substrate (ITO layer + glass layer).

[0224] 2) Spin coating a zinc oxide precursor solution at a rotation speed of 2000 rpm for 1 minute; and then annealing at 100° C. for 10 minutes to obtain an electron transport layer.

[0225] 3) Spin coating a quantum dot liquid, wherein the quantum dot content in the quantum dot liquid is 20 mg / mL, the rotation speed is 2000 rpm, and the rotation time is 1 minute; then annealing at 100° C. for 10 minutes to form a quantum dot light-emitting layer.

[0226] 4) A stable hole transport layer was formed by evaporation. The source material was a mixture of CBP and COT-modified CPB (1:1) at an evaporation rate of 1 nm / min, with a total evaporation thickness of 50 nm.

[0227] 5) Evaporated cathode, the material is molybdenum oxide / silver, with a thickness of 3nm / 100nm.

[0228] The present disclosure also provides a display panel comprising any of the thin-film light-emitting devices described in the aforementioned thin-film light-emitting device embodiments. The display panel can be a smartphone screen, a smartwatch screen, or another type of display screen. Because the display panel comprises any of the thin-film light-emitting devices described in the aforementioned thin-film light-emitting device embodiments, it exhibits the same beneficial effects and is not further detailed herein.

[0229] Other embodiments of the present disclosure will readily occur to those skilled in the art after considering the specification and practicing the invention disclosed herein. This disclosure is intended to cover any variations, uses, or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary techniques in the art not disclosed herein. The description and examples are to be considered as exemplary only, with the true scope and spirit of the present disclosure being indicated by the appended claims.

Claims

1. A thin film light emitting device comprising an anode, a hole transport layer, a light emitting layer and a cathode stacked in sequence; The hole transport layer contains a hole transport material and a triplet quenching material, wherein the triplet quenching material can quench at least part of triplet excitons in the hole transport material; in, The triplet quenching material comprises a linking group and at least one quenching group connected to the linking group, and the structure of the quenching group is selected from the following structures: Ar1 and Ar2 are each independently selected from a substituted or unsubstituted aryl group having 6 to 30 carbon atoms, or a substituted or unsubstituted heteroaryl group having 4 to 30 carbon atoms; R1 is selected from deuterium, alkyloxycarbonyl having 1 to 18 carbon atoms, alkylcarbonyl having 1 to 18 carbon atoms, alkoxy having 1 to 18 carbon atoms, alkyl having 1 to 18 carbon atoms, cycloalkyloxycarbonyl having 5 to 10 carbon atoms, cycloalkylcarbonyl having 5 to 10 carbon atoms, cycloalkyloxy having 5 to 10 carbon atoms, cycloalkyl having 5 to 10 carbon atoms, substituted or unsubstituted aryl having 6 to 18 carbon atoms, substituted or unsubstituted heteroaryl having 4 to 18 carbon atoms; m is a positive integer selected from 0-7.

2. The thin film light emitting device according to claim 1, wherein: The number of quenching groups in the triplet quenching material is 2 to 4.

3. The thin film light emitting device according to claim 1, wherein: The quenching group of the triplet quenching material is selected from The connecting group of the triplet quenching material has an aromatic structure, and the quenching group is directly connected to the aromatic structure.

4. The thin film light emitting device according to claim 3, wherein: The Ar1 and Ar2 are each independently selected from substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted biphenyl; When Ar1 or Ar2 has a substituent, any of the substituents is selected from deuterium, Methyl, ethyl, isopropyl.

5. The thin film light emitting device according to claim 3, wherein: The linking group is selected from substituted or unsubstituted biphenyl, substituted or unsubstituted spirofluorenyl, substituted or unsubstituted terphenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted anthracenyl, substituted or unsubstituted phenanthrenyl, substituted or unsubstituted phenyl; When the linking group has a substituent, any one of the substituents is independently selected from deuterium, methyl, ethyl, and isopropyl.

6. The thin film light emitting device according to claim 3, wherein: The triplet quenching material is selected from 4,4'-di(2,2-diphenylvinyl)-1,1'-biphenyl and 2,2',7,7'-tetrakis(2,2-diphenylvinyl)spiro-9,9'-difluorene.

7. The thin film light emitting device according to claim 1, wherein: The quenching group of the triplet quenching material is selected from The molecular weight of the triplet quenching material is between 600 and 1200.

8. The thin film light emitting device according to claim 7, wherein: The connecting group is an organic semiconductor structure with hole transport properties; or the connecting group is a flexible connecting group with at least two flexible branches, and any one of the flexible branches is connected to one of the quenching groups.

9. The thin film light emitting device according to any one of claims 1 to 8, wherein: The HOMO energy level of the triplet quenching material is not greater than the HOMO energy level of the hole transport material.

10. The thin film light emitting device according to any one of claims 1 to 8, wherein: The difference between the LUMO energy level of the triplet quenching material and the LUMO energy level of the hole transport material is not less than -1 eV.

11. The thin film light emitting device according to claim 10, wherein: The LUMO energy level of the triplet quenching material is not less than the LUMO energy level of the hole transporting material.

12. The thin film light emitting device according to any one of claims 1 to 8, wherein: The hole mobility of the triplet quenching material is smaller than the hole mobility of the hole transporting material.

13. The thin film light emitting device according to any one of claims 1 to 8, wherein: The triplet energy level of the triplet quenching material is smaller than the triplet energy level of the hole transporting material.

14. The thin film light emitting device according to any one of claims 1 to 8, wherein: The singlet energy level of the triplet quenching material is greater than the singlet energy level of the hole transporting material.

15. The thin film light emitting device according to any one of claims 1 to 8, wherein: The mass ratio of the triplet quenching material in the hole transport layer is between 0.0001% and 90%.

16. The thin film light emitting device according to claim 15, wherein: The mass ratio of the triplet quenching material in the hole transport layer is between 1% and 30%.

17. The thin film light emitting device according to claim 15, wherein: The mass ratio of the triplet quenching material in the hole transport layer is between 2% and 10%.

18. The thin film light emitting device according to any one of claims 1 to 8, wherein: The hole transport material is an organic semiconductor material; the light-emitting layer is a quantum dot light-emitting layer.

19. The thin film light emitting device according to any one of claims 1 to 8, wherein: The thin film light emitting device is a blue light thin film light emitting device.

20. A display panel comprising the thin film light emitting device according to any one of claims 1 to 19.